2019
DOI: 10.18632/oncotarget.26623
|View full text |Cite
|
Sign up to set email alerts
|

An ingenious non-spherical mesoporous silica nanoparticle cargo with curcumin induces mitochondria-mediated apoptosis in breast cancer (MCF-7) cells

Abstract: Curcumin delivery to cancer cells is challenging due to its hydrophobic nature, low bio distribution and low availability. Many nano vehicles suffer from low stability and toxicity, and hence the prerequisite of a non-toxic nano vehicle with effective drug delivery is still being delved. The present study investigates the delivery efficiency of curcumin with non-spherical mesoporous silica nanoparticles (MSNAs). Their mechanism of drug delivery and signalling proteins activated to induce apoptosis was further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Curcumin is hypothesized to mediate tumor cell apoptosis through these exogenous pathways. Synthetic curcumin non-spherical mesoporous silica nanoparticles can increase the carrying capacity and saturability of curcumin (35). In-depth studies have shown that curcumin binds apoptotic proteins, such as caspase-3 (36), phosphatase and tensin homolog deleted from chromosome 10 and poly ADP-ribose polymerase (37), inducing mitochondrial damage and thereby promoting tumor cell apoptosis (35).…”
Section: Curcumin and Tumor Proliferation Previous Studies Havementioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin is hypothesized to mediate tumor cell apoptosis through these exogenous pathways. Synthetic curcumin non-spherical mesoporous silica nanoparticles can increase the carrying capacity and saturability of curcumin (35). In-depth studies have shown that curcumin binds apoptotic proteins, such as caspase-3 (36), phosphatase and tensin homolog deleted from chromosome 10 and poly ADP-ribose polymerase (37), inducing mitochondrial damage and thereby promoting tumor cell apoptosis (35).…”
Section: Curcumin and Tumor Proliferation Previous Studies Havementioning
confidence: 99%
“…Synthetic curcumin non-spherical mesoporous silica nanoparticles can increase the carrying capacity and saturability of curcumin (35). In-depth studies have shown that curcumin binds apoptotic proteins, such as caspase-3 (36), phosphatase and tensin homolog deleted from chromosome 10 and poly ADP-ribose polymerase (37), inducing mitochondrial damage and thereby promoting tumor cell apoptosis (35). Another synthetic nanomaterial, chitosan nanoparticles loaded with demethoxycurcumin in combination with cisplatin, downregulates the expression levels of thymidine phosphorylase required for DNA self-repairing pyrimidine salvage pathways and induces apoptosis in non-small cell lung cancer (NSCLC) cell lines (38).…”
Section: Curcumin and Tumor Proliferation Previous Studies Havementioning
confidence: 99%
“…Lycorine stimulates mitochondrial-mediated apoptosis by up-regulation of ROCK1 [112]. Taking everything into account, it seems that naturally occurring compounds are able to target mitochondrial function in the induction of apoptosis in cancer cells [113,114].…”
Section: Mitochondria and Cancermentioning
confidence: 99%
“…Co-delivery of curcumin and doxorubicin using core-shell nanoparticles (NPs) with hydrophobic PLLA core loaded with curcumin (Cur) and hydrophilic heparin shell adsorbing doxorubicin (DOX) exhibits promising results for effective breast tumor inhibition [156]. Various research groups have developed nanoparticles containing curcumin alone or in combination with chemotherapies to enhance therapeutic efficacy and bioavailability [157,158,159]. Development of curcumin-loaded solid nanoparticles (Cur-SLN) [157], non-spherical mesoporous silica nanoparticles (MSNAs) [158], and HER2 aptamer-decorated curcumin-loaded human serum albumin nanoparticle (Apt-HSA/CCM NP) [159] are just few examples of nanoparticle approaches.…”
Section: Curcumin the Golden Spicementioning
confidence: 99%